Tallgrass prairie plant responses to seasonal timing of prescribed fire - Glidden, Alec (My University, 2026)
Tallgrass prairie is among the most endangered ecosystems in North America, and the remaining prairie landscapes are increasingly threatened by woody encroachment, often as a result of altered disturbance regimes. Prescribed fire is widely used to maintain an open grassland state and limit woody encroachment; however, contemporary management practices concentrate prescribed burning in a narrow spring window. This not only contrasts with historical fire regimes but also homogenizes grassland communities and exacerbates air quality issues both locally and regionally. Burning outside the traditional spring window may provide unique opportunities for conservation and restoration. The overarching goal of my research was to examine how the timing of prescribed fire influences the tallgrass prairie ecosystem at multiple spatial and temporal scales using a combination of short- and long-term experiments conducted at Konza Prairie Biological Station. I first evaluated the long-term effects of prescribed fire applied in different seasons (annual burning in spring, fall, and winter, and biennial burning in summer) on tallgrass prairie plant communities using data from a 31-year experiment. I found that repeated burning in different seasons significantly altered plant community composition, native species richness and diversity, and functional group dynamics over time. Annual spring burning promoted high cover of the dominant warm-season grasses and reduced native species richness and diversity, while summer burning supported greater native species richness and diversity and increased cool-season graminoid cover. Plant community responses to fall or winter fires were generally intermediate relative to spring and summer, but with greater legume cover. Many responses varied with topographic position (uplands vs. lowlands) and exhibited delayed or non-linear dynamics that emerged only after years of repeated fire treatments. The second objective of my research was to determine how these same fire treatments affected aboveground net primary productivity (ANPP), precipitation-productivity relationships, and the cumulative effects of repeated burning on soil properties. Despite pronounced differences in plant community composition, annual burning in spring, fall, and winter dormant seasons yielded similar levels of graminoid and total ANPP over three decades. Biennial summer burning reduced mean ANPP in lowlands relative to dormant-season fire, although responses varied depending on whether comparisons with dormant-season treatments were made in burned versus non-burned years. Across all burn seasons, ANPP was strongly positively associated with growing-season precipitation, and fire timing did not alter the sensitivity of productivity to interannual climate variability. Soil properties differed primarily between topographic positions rather than among fire treatments. Collectively, these results suggest that environmental factors such as interannual climate variability and topographic gradients exerted stronger controls on ecosystem functioning than the seasonal timing of prescribed fire. Last, I established a new field experiment to investigate the effects of reintroducing annual fire in contrasting seasons (spring vs. late-summer) in a bison-grazed, shrub-encroached grassland previously managed under a 4-year fire return interval. I established vegetation transects in lowland and upland positions to evaluate the short-term effects of an increase in fire frequency in different seasons and established baseline data for longer-term measurements. In addition to these watershed-scale measurements, I implemented plot-scale treatments that included mowing prior to burning and grazing exclosures to restrict access by bison. I found that herbaceous communities responded in broadly similar ways to reintroducing annual fire, regardless of the seasonal timing of fires. Annual fires increased warm-season grass cover, but also slightly reduced cover of cool-season graminoids and forbs. Across the watershed, clonal shrub responses to season of fire diverged after the second fire application. Specifically, a repeated summer burn was less effective than a repeated spring burn at reducing the size of clonal shrub patches. When assessing combined treatments at the plot level, we did not detect any additive or synergistic effects of burn season, grazing, or mowing on Cornus drummondii shrub islands. Despite complete removal of aboveground tissue at the time of mowing, the effects of mowing were limited to a transient increase in stem recruitment. The presence of grazers reduced herbaceous cover in and around shrub islands, which could alter the effectiveness of subsequent fires; however, stem density of C. drummondii increased regardless of bison presence. The effects of two years of annual burning were offset by rapid stem regrowth despite reductions in aboveground biomass, with most responses occurring at the grass-shrub boundary. Collectively, my results highlight that the seasonal timing of fire is an important but underutilized driver of tallgrass prairie ecosystem structure and function. Prescribed burning in different seasons altered plant community composition, diversity, productivity, and woody plant dynamics, while interactions with topography, climate variability, and grazing strongly mediated these responses. Expanding prescribed fire beyond spring may provide opportunities to increase landscape heterogeneity, diversify management outcomes, and improve grassland conservation and restoration from woody encroachment, while maintaining key ecosystem functions of the tallgrass prairie.
Keywords: Fire season; Grasslands; Grassland management; Prescribed fire; Tallgrass prairie